Mortality among young Nicaraguan immigrants to Costa Rica: deaths from disease versus injury - Bonilla, Roger E. (Universidad de Costa Rica, 2015)
The aim of this research was to investigate mortality among young Nicaraguan immigrants to Costa Rica (disease versus injury deaths) and compare it with the young native population. The study focused on persons aged 15 to 34 years, due to the relative importance of the injury deaths in this age group. Deaths (numerators) and population data (denominators), which were obtained from the 10th Population and Housing Census 2000, were used to calculate the mortality rates per 100,000 inhabitants. The relative risk (RR) results from dividing each set of causal standardized mortality rates. Approximately 66% of deaths among Nicaraguan immigrants are injury deaths versus 57% for the native population. Immigrants have higher relative risks (RR) of mortality than natives for injury deaths (homicides RR=2.00, other accidents RR=1.70, and vehicular accidents RR=1.17). We emphasize that Nicaraguan immigrants have twice the risk of dying from homicide than the native population.